Actuator and Sensor Positioning Optimization in Control Design for a Large BWB Passenger Aircraft. (26th June 2011) - Schirrer, A.; Westermayer, C.; Hemedi, M.; Kozek, M.
Abstract : This paper states an approach to actuator and sensor positioning optimization and design in the control system design of a large blended wing body (BWB) passenger aircraft. Numerous objectives have to be achieved by the control system: loads alleviation, vibration attenuation, and the fulfillment of handling quality requirements. Exploiting the system structure and existing system knowledge (excitation, comfort, and load formulations), evaluation criteria are designed to assess actuator and sensor effectiveness and efficiency for the aircraft dynamic range of interest. The tasks of optimal actuator and sensor positioning, actuator sizing, and actuator bandwidth requirements are investigated, whereby solutions that are robust are sought with respect to parameter variations. The results are shown on a BWB passenger aircraft model and verified using a normalized closed-loop performance assessment approach.